PHYLOGENETIC ORIGINS OF ANTIBODY STRUCTURE : II. IMMUNOGLOBULINS IN THE PRIMARY IMMUNE RESPONSE OF THE BULLFROG, RANA CATESBIANA - Marchalonis, J. (The Rockefeller University Press, 1966)
The anuran amphibian, Rana catesbiana, has been found to possess at least two kinds of immunoglobulins corresponding to γG- and γM-classes. These classes have the same chain structures as those of their counterparts in higher animal species. Light chains of both immunoglobulins had molecular weights of 20,000. Heavy chains of the γM-class had molecular weights of 72,100; those of the γG-class had molecular weights of 53,600. The carbohydrate content of the γG-immunoglobulin was 2.1%, and that of the γM-protein was 10.8%. The amino acid compositions of the immunoglobulins were generally similar to those of mammalian immunoglobulins. After a single injection of phage antigen (f2), the order of appearance of phage-neutralizing activity in the frog immunoglobulin classes was (a) γM-antibodies, and (b) γG-antibodies. The results of this and previous studies suggest that the γG-immunoglobulins emerged at some point in evolution between the elasmobranchs and the anuran amphibians.